Free radical scavenging effect of Trichodesma amplexicaule against renal vascular complications in diabetic Rats - Srinivas Rao Avanapu; Dachani Sudharshan Reddy; Pradeep Hulikare Ananth (International Journal of Phytomedicine, 2012)
Objective: The aim of the present study was to investigate the antioxidant and renal protective effect of Trichodesma amplexicaule extract in streptozotocin-induced diabetic rats. Methods: Wistar rats were randomly divided into five groups: Normal control, diabetic control and Trichodesma amplexicaule (100 and 200mg/kg) and glibenclamide treated groups. Blood glucose, Total Cholesterol, Triglycerides, Aminotransferases, kidney functions and kidney oxidant/antioxidants status were estimated. Streptozotocin effectively altered the biochemical, histoarchitecture, malondialdehyde and antioxidant enzyme levels, while Trichodesma amplexicaule ameliorated their levels in the treated group. Results: Oral treatment with methanolic extract for 4 weeks reduced significantly Blood glucose, Total Cholesterol, Triglycerides, Aminotransferases, kidney function parameter levels in diabetic animals. Furthermore, the biochemical findings were supplemented with histopathological examination of pancreas and kidney. Histological observation of kidney of diabetic rats showed degenerative changes in glomerulus and renal tubules and extract treatment rejuvenated kidney histoarchitecture. Results of this study suggest that Trichodesma amplexicaule offered significant protection against oxidative stress induced by Streptozotocin, as noted by increase in superoxide dismutase and catalase along with decrease in lipid peroxidation levels. Conclusion: The present work provide scientific evidence of the preventive and therapeutic potential of Trichodesma amplexicaule against kidney disorder in diabetes and thus may provide a promising drug for managing diabetic kidney disorders and assumes that activity may be due to the prominent antioxidant property shown by Trichodesma amplexicaule.